Parental Environment Quality, Mother-Child Attachment, and Cognitive Development of Preschool Children with Working Mother - Saniatu Aini; Neti - Hernawati (Journal of Child Development Studies, 2016)
This research aimed to analyze parental environment quality, attachment between mother and children, cognitive development, and correlation among those variables. This research took place at Tanah Sareal and Bogor Barat, Bogor City and involved 39 children at preschool age with their mom chosen by purposive method. Data were collected by interview using structure questionnaire and observation. Data were analyzed by descriptive analysis and correlation. More than 50 percent children have the medium score of the parental environment quality,  attachment at average category, and cognitive development. Mothers education were correlated significantly positive with parental environment quality, learning, and attachment.